2018
DOI: 10.1007/s11606-018-4608-2
|View full text |Cite
|
Sign up to set email alerts
|

Engaging High-Need Patients in Intensive Outpatient Programs: A Qualitative Synthesis of Engagement Strategies

Abstract: Promising clinical, interpersonal, and population-based approaches to engaging high-need patients frequently deviate from standard practice and require creative and proactive staff with adequate time, resources, and flexibility to address patients' needs on patients' terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…26 In another study interviewing clinicians and leaders across 12 intensive outpatient programmes, three key facilitators of patient engagement emerged: (1) financial assistance and other resources to help meet basic needs, (2) working as a multi-disciplinary care team and (3) adequate time and resources to develop close relationships focused on patient goals. 27 Our results concur on the importance of a multi-disciplinary approach, establishing trusting relationships, and pursuing patient-centred goals. Our results diverge on the role of resources to meet basic needs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…26 In another study interviewing clinicians and leaders across 12 intensive outpatient programmes, three key facilitators of patient engagement emerged: (1) financial assistance and other resources to help meet basic needs, (2) working as a multi-disciplinary care team and (3) adequate time and resources to develop close relationships focused on patient goals. 27 Our results concur on the importance of a multi-disciplinary approach, establishing trusting relationships, and pursuing patient-centred goals. Our results diverge on the role of resources to meet basic needs.…”
Section: Discussionsupporting
confidence: 79%
“…For example, interdisciplinary staff in a qualitative study of an ambulatory intensive care centre also identified warm relationships between patients and staff as a marker of success 26. In another study interviewing clinicians and leaders across 12 intensive outpatient programmes, three key facilitators of patient engagement emerged: (1) financial assistance and other resources to help meet basic needs, (2) working as a multi-disciplinary care team and (3) adequate time and resources to develop close relationships focused on patient goals 27. Our results concur on the importance of a multi-disciplinary approach, establishing trusting relationships, and pursuing patient-centred goals.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our final finding suggests that A-ICU team members view their proximal goal as increased engagement rather than reducing utilization. As a recent study highlighted, 22 success of intensive outpatient programs may be predicated on the ability to improve patient participation in their health care. Their findings of how intensive primary care programs improve engagement parallel our findings: the importance of multidisciplinary team composition, having requisite time and resources, and flexible approaches to patient goals.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Perhaps because the VHA is an integrated system, providers did not find poor coordination to be the most important factor. Instead, non-adherence, lack of engagement (defined here as a patient's participation in self-care and other health-related activities, motivation and ability to address health issues, and shared decision-making [25][26][27] ) and behavioral health issues dominated.…”
Section: Lesson #2: Top Reasons For Preventable Emergency Department (Ed) Visits and Hospi-talizations Were Not Due To Uncoordinated Carementioning
confidence: 99%